Effects of sodium chloride on adsorption at different interfaces and aggregation behaviors of disulfonate gemini surfactants. Issue 17 (3rd February 2016) - Jiao, Tiliu; Liu, Xiaochen; Niu, Jinping
Abstract : Schematic illustration of NaCl effects on the adsorption of C n -DADS molecules at different interfaces (Cl − is not shown). Abstract : Effects of NaCl on adsorption of dialkylated diphenyl ether disulfonate gemini surfactants (C n -DADS, n = 8, 10 and 12) at different interfaces were studied by equilibrium surface tension, dynamic surface tension, interfacial tension and wetting measurements. The results show that the critical micelle concentration (cmc) values of C n -DADS aqueous solutions decrease with an increase in NaCl concentration. For C8 -DADS aqueous solution, the values of the surface tension at cmc ( γ cmc ) keep almost invariable with the addition of NaCl. The monomer diffusion coefficient ( D eff ) values of C n -DADS increase with an increase in both alkyl chain length and inorganic salt concentration. The interfacial tensions (IFTs) between C n -DADS solutions with various amount of NaCl added and dodecane slightly decrease with the increase of NaCl concentration. The equilibrium contact angle values decrease significantly firstly and then no further change with increasing the NaCl concentration. The vesicles are formed in both 0.5 mM C8 -DADS aqueous solution and 2 mM C8 -DADS solution with 0.1 M NaCl.